The Role of Open Distance Learning in Lifelong Learning: Opportunities and Challenges - Lehloka, Motlatsi Cletus (Journal of Ecohumanism, 2025)
Open distance learning (ODL) supports lifelong learning by providing accessibility and flexibility, as well as designating pathways for continued professional development. It allows an individual to acquire new knowledge and skills during their life, regardless of age, location, or previous education. This continued learning is critical to keep pace with an economy that is changing quickly, and it supports individuals in their development and career pathways. Of particular importance, the integration of open educational resources (OER), into an ODL framework can help to significantly increase access to quality resources and can help to facilitate affordable education. Firstly, institutions that are largely dependent on developing their own teaching and learning resources can use OER to reduce costs, development time, and increase the quality and accessibility of teaching and learning resources. Although distance learning offers opportunities for lifelong learning, it presents several significant challenges which include technical challenges, time management challenges, communication challenges, and ensuring appropriate quality assurance. This paper intents to examine the role of ODL in facilitating the lifelong learning within social science identifying both the opportunities it presents and challenges it faces. The study used a qualitative research approach, as well as detailed literature reviews and case studies in the ODL sector. The findings highlight that ODL does not only facilitates flexibility access to education but also supports the principles of sustainable education, promotes inclusivity and offers diverse learning style. This study offers useful insights for educators interested in using ODL to enhance sustainable lifelong learning.